Cu-catalyzed one-pot multicomponent approach for the synthesis of symmetric and asymmetric 1, 4-dihydropyridine (1, 4-DHP) linked 1, 2, 3-triazole derivatives. Issue 13 (2nd July 2020) - Kaushik, Preeti; Kumar, Ajit; Kumar, Prashant; Kumar, Sandeep; Singh, Brajendra Kumar; Bahadur, Vijay
Abstract: Synthesis of various symmetric and asymmetric 1, 4-DHP linked 1, 2, 3-triazole derivatives from economical and readily available starting materials via a convenient methodology in a single-pot method using CuSO4 ·5H2 O as an efficient catalyst has been reported. The reaction proceeded efficiently under the optimized reaction conditions with excellent functional group compatibility providing the desired products in good yields. The method appears to be an efficient combinatorial strategy for the synthesis of new 1, 4-DHP linked triazole derivatives. Graphical Abstract: